2014
DOI: 10.1016/j.jchromb.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Protein solubilization: A novel approach

Abstract: Formulation development presents significant challenges with respect to protein therapeutics. One component of these challenges is to attain high protein solubility (> 50 mg/ml for immunoglobulins) with minimal aggregation. Protein-protein interactions contribute to aggregation and the integral sum of these interactions can be quantified by a thermodynamic parameter known as the osmotic second virial coefficient (B-value). The method presented here utilizes high-throughput measurement of B-values to identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Trehalose is a disaccharide formed by a 1,1-glucoside bond between two α-glucose units, freely soluble in water, and used as a carrier to increase protein stability, trehalose is used with protein formulations to prevent degradation and to enhance proteins’ stability [ 30 ] and it was used in this study to investigate its effect on drug dissolution.…”
Section: Introductionmentioning
confidence: 99%
“…Trehalose is a disaccharide formed by a 1,1-glucoside bond between two α-glucose units, freely soluble in water, and used as a carrier to increase protein stability, trehalose is used with protein formulations to prevent degradation and to enhance proteins’ stability [ 30 ] and it was used in this study to investigate its effect on drug dissolution.…”
Section: Introductionmentioning
confidence: 99%
“…Comparable effects to previous studies were observed, where chaotropic salts and increasing ionic strength decreased predominant attractive interactions and enhanced protein solubility. In contrast, very little data are available for protein solubility dependent on other additives . Besides the effect of pH and buffer salts, valuable data are presented in this study about the influence of sugars, amino acids or surfactants on protein solubility without the influence of pH and ionic strength.…”
Section: Discussionmentioning
confidence: 99%
“…A widely recognized approach uses protein–protein interactions (PPI) to predict solubility behaviour of proteins. While attractive interactions are unfavourable, repulsive interactions are preferred during HCF development, as they increase protein solubility . Most investigations were performed under dilute conditions utilizing the second virial coefficient, B 22 .…”
Section: Introductionmentioning
confidence: 99%
“…224,225 Among many different ways to obtain B 22 values, such as selfinteraction chromatography (SIC), 226 membrane osmometry (MO) 227 and analytical ultracentrifugation (AUC), 228 the most common method is through static light scattering (SLS). 225,229,230 Recently this value was used to determine a universal solubility line, the "liquidus" line, as part of a phase diagram for a mAb. 231,232 Cross-interaction chromatography (CIC) assay, introduced by Jacob et al 233 takes advantage of the accumulative effect on a column to capture weak binding between testing mAb and a large quantity (30 mgs) of immobilized human serum IgGs.…”
Section: Solubilitymentioning
confidence: 99%